Cognitive Abilities and Mathematical Competencies at School Entry. Issue 4 (18th December 2017) - Ribner, Andrew; Moeller, Korbinian; Willoughby, Michael; Blair, Clancy; ,
ABSTRACT: The aim of this study was to identify mathematical competencies in early childhood and cognitive correlates of those competencies in a prospective longitudinal sample of children ( N = 1, 292) in predominantly low‐income and nonurban communities in the United States. General mental ability, processing speed, vocabulary, and the working memory (WM), inhibitory control (IC), and cognitive flexibility components of executive function (EF) were assessed when children were aged 4 and 5 years. Math ability was assessed prior to school entry using a norm‐referenced assessment. Exploratory factor analysis indicated that items from the math assessment loaded onto factors representing conceptual and procedural skill. General mental ability, processing speed, vocabulary, and a unitary EF composite all related to both conceptual and procedural skill. When EF components were examined separately, however, only the IC aspect of EF was related to conceptual skill and only the WM aspect of EF was related to procedural skill.